China's Accession to the World Trade Organization : The Services Dimension - Mattoo, Aaditya, 1961- 1961- (The World Bank, 2002)
China's General Agreement on Trade in Services (GATS) commitments represent the most radical services reform program negotiated in the World Trade Organization. China has promised to eliminate over the next few years most restrictions on foreign entry and ownership, as well as most forms of discrimination against foreign firms. These changes are in themselves desirable. However, realizing the gains from, and perhaps even the sustainability of, liberalization will require the implementation of complementary regulatory reform and the appropriate sequencing of reforms. Three issues, in particular, merit attention: • Initial restrictions on the geographical scope of services liberalization could encourage the further agglomeration of economic activity in certain regions—to an extent that is unlikely to be reversed completely by subsequent countrywide liberalization. • Restrictions on foreign ownership (temporary in most sectors but more durable in telecommunications and life insurance) may dampen the incentives of foreign investors to improve firm performance. • Improved prudential regulation and measures to deal with the large burden of nonperforming loans on state banks are necessary to deliver the benefits of liberalization in financial services. And in basic telecommunications and other network-based services, meaningful liberalization will be difficult to achieve without strengthened pro-competitive regulation. This paper—a product of Trade, Development Research Group—is part of a larger effort in the group to assess the implications of services trade reform. This research is supported in part by the U.K. Department for International Development